Les rois, les poètes et les psaumes. Sur quelques contextes des premières mise en vers français du Psautier (c. 1540–c. 1550) - Petey-Girard, Bruno (Viator (English and Multilingual Edition), 2012)
Abstract The translation of the Psalms into French verse during the Renaissance is often studied through the prism of Reformation spiritual dynamics. It is indeed in Geneva at the heart of the Reformed Church that the Psalms experienced an enduring success. However, one should not forget that Clément Marot offered his versed translation of the Psalms to Francis I, the Catholic king of France, and that, therefore, a similar work explicitly crafted for the spiritual revival of catholic believers could have also been presented to Henry II. The French monarchy did not seize this opportunity that presented itself between 1540 and 1560 to sponsor the creation of a French verse catholic psalm book. Various reasons can be linked to the failure of a timely use of the Psalms by the French Crown and a much too tardy understanding of the poetic genius of the Psalms.